2023
DOI: 10.1007/s00417-023-06241-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of functional and morphologic changes between brolucizumab and faricimab in neovascular age-related macular degeneration

Maiko Maruyama-Inoue,
Yasuo Yanagi,
Tatsuya Inoue
et al.

Abstract: Purpose This study aimed to compare functional and morphologic changes in the loading phase between patients with treatment-naïve macular neovascularization (MNV) due to neovascular age–related macular degeneration (nAMD) treated with either intravitreal brolucizumab (IVBr) or intravitreal faricimab (IVF) injections in a clinical setting. Methods We retrospectively studied 92 consecutive eyes of 90 patients with neovascular nAMD who were scheduled to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Moreover, 44.9% (TENAYA) and 45.7% (LUCERNE) of patients were on 16-week dosing intervals [13]. Maruyama Inoue et al [10] evaluated comparatively the outcomes of faricimab (Vabysmo TM , Roche, 6 mg/0.05 mL) and brolucizumab (Beovu ® , Novartis, 6 mg/0.05 mL), after 3 monthly intravitreal injections, on 90 patients and found similar results. No differences were observed either in BCVA mean gain or decrease of CRT.…”
Section: Ivf In Naïve Patients With Namdmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, 44.9% (TENAYA) and 45.7% (LUCERNE) of patients were on 16-week dosing intervals [13]. Maruyama Inoue et al [10] evaluated comparatively the outcomes of faricimab (Vabysmo TM , Roche, 6 mg/0.05 mL) and brolucizumab (Beovu ® , Novartis, 6 mg/0.05 mL), after 3 monthly intravitreal injections, on 90 patients and found similar results. No differences were observed either in BCVA mean gain or decrease of CRT.…”
Section: Ivf In Naïve Patients With Namdmentioning
confidence: 88%
“…Six studies reported data on naïve nAMD treated with IVF [4,10,12,13,16,25], either as single arm [16,25], or as multiple arms studies [4,10,12,13], proving data supporting non-inferiority of IVF to other anti-VEGF, such as aflibercept, ranibizumab and brolucizumab, in terms of functional and anatomic outcomes. Moreover, Heier et al [13], in the phase 3 study TENAYA and LUCERNE, found that the results could be maintained with up to 16 weeks interval between injections, after a loading period of 4 injections monthly, which would be a significant decreased burden on the patients with nAMD.…”
Section: Ivf In Naïve Patients With Namdmentioning
confidence: 99%
See 3 more Smart Citations